Penyisihan, Warna, Zat Organik Dan Kekeruhan Pada Air Gambut Dengan Kombinasi Proses Koagulasi-Flokulasi Menggunakan Koagulan Aluminium Sulfat (Al2(So4)3) Dan Membran Ultrafiltrasi - Nastiti, Yulia; Daud, Syarfi; Herman, Syamsu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The main challenge in peat water treatment is finding the treatment process that produces treated water quality which meets the quality standard of clean water. One of the peat water treatment is membrane ultrafiltration with combination coagulation-flocculation process. Combination treatment is done to improve the quality of processed water and reduce the workload of the membrane so membrane's performance increases. The purpose of this study was to determine the decrease of turbidity, organic matter and color on coagulation-flocculation process, determine the flux and rejection coefficient of turbidity, organic matter and color in processing using ultrafiltration membranes without and with combination coagulation-flocculation process and determine decrease of color, organic matter, and turbidity in water treatment using membrane ultrafiltration with combination of coagulation-flocculation process. The study was conducted by using 60 mg/L of coagulant aluminum sulfate (Al2(SO4)3) on coagulation-flocculation process and ultrafiltration membrane feed pressure 0.5; 1 and 1.5 bar. The results showed highest rejection coefficient values of turbidity, organic matter and color obtained on peat water treatment by combination coagulation-flocculation process and ultrafiltration membrane at pressure 0.5 bar, with rejection coefficient value for turbidity, organic matter and color respectively amounted to 100 %, 91.04% and 96.68%.Key Words: Aluminum Sulfate, Coagulation-Flocculation, Color, Organic Matter, Peat Water, Turbidity, Ultrafiltration Membrane